Tripling the Optical Efficiency of Color-Converted Micro-LED Displays with Funnel-Tube Array - Fangwang Gou; En-Lin Hsiang; Guanjun Tan; Yi-Fen Lan; Cheng-Yeh Tsai; Shin-Tson Wu (Crystals, 2019)
Color-converted micro-LED displays consist of a mono-color micro-LED array and color conversion materials to achieve full color, while relieving the burden of epitaxial growth of three-color micro-LEDs. However, it usually suffers from low efficiency and color crosstalk due to the limited optical density of color conversion materials. With funnel-tube array, the optical efficiency of the color-converted micro-LED display can be improved by ~3X, while the crosstalk is eliminated. After optimization of the tapper angle, the ambient contrast ratio is also improved due to higher light intensity.